Judaism, Christianity, Islam and the Baha'i Faith: An Introduction to Abrahamic Religions - Lillian Dare (CreateSpace Independent Publishing Platform, 2014)
An introduction to the idea and development of god-s and religion-s; followed by information on 'Abrahamic Religions' and the structure of their Holy Scriptures
Keywords: Abrahamic Religions -- Baha'i Faith